2006
DOI: 10.1084/jem2035oia14
|View full text |Cite
|
Sign up to set email alerts
|

The activity status of cofilin is directly related to invasion, intravasation, and metastasis of mammary tumors

Abstract: nderstanding the mechanisms controlling cancer cell invasion and metastasis constitutes a fundamental step in setting new strategies for diagnosis, prognosis, and therapy of metastatic cancers. LIM kinase1 (LIMK1) is a member of a novel class of serine-threonine protein kinases. Cofi lin, a LIMK1 substrate, is essential for the regulation of actin polymerization and depolymerization during cell migration. Previous studies have made opposite conclusions as to the role of LIMK1 in tumor cell motility and metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
118
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(121 citation statements)
references
References 27 publications
1
118
2
Order By: Relevance
“…3), it was found to be significantly increased compared with non-invasive tumour cells from the same tumour with normal levels of LIMK1 and cofilin expression 43 . Furthermore, increasing the expression of LIMK1 alone in these mammary tumour cells inhibited the cofilin pathway and inhibited invasion and metastasis 43 . In mice with polyoma middle T oncogene (PyMT)-derived mammary tumours, invasive cells have increased expression of both LIMK1 and SSH, but not cofilin.…”
Section: The Cofilin Pathway In Tumour Invasionmentioning
confidence: 93%
See 4 more Smart Citations
“…3), it was found to be significantly increased compared with non-invasive tumour cells from the same tumour with normal levels of LIMK1 and cofilin expression 43 . Furthermore, increasing the expression of LIMK1 alone in these mammary tumour cells inhibited the cofilin pathway and inhibited invasion and metastasis 43 . In mice with polyoma middle T oncogene (PyMT)-derived mammary tumours, invasive cells have increased expression of both LIMK1 and SSH, but not cofilin.…”
Section: The Cofilin Pathway In Tumour Invasionmentioning
confidence: 93%
“…Unicellular organisms such as yeasts usually have only one ADF/cofilin-type protein, whereas multicellular organisms typically have several isoforms. In some cultured mammalian cell lines 40 and invasive mammary tumour cells 10,43 , cofilin 1 is the most abundant isoform, whereas ADF is expressed at much lower levels (5%). Therefore, for this Review 'cofilin' will refer to cofilin 1, the most abundant isoform found in invasive mammary tumour cells 10,12 .…”
Section: Biochemistry Of the Cofilin Pathwaymentioning
confidence: 99%
See 3 more Smart Citations